Development of USARB Scientiﬁc Library collections in the years 2010-2017 (Confluenţe Bibliologice, 2019)
This article discusses the importance of building collections and the value of the information and documentation function of the university library. The library being the only academic structure that provides users with access to useful information on various information media: printed and electronic.
Keywords: donations; collection development; current and retrospective acquisitions